The Use of Flashcards in Teaching English for the Sixth Year Students of SDN 1 Tuntang in the academic year of 2002 - 2003 - Insaniyah Insaniyah (IAIN Salatiga, 2008)
This research is to study the use of flashcards to teach English vocabulary. Teaching material in above is virtually concerning with visual aids. By using visual aids, expected that the teachers would be able to motivate them to learn and pay deep attention to the presentable materials by the teachers, so the students will not be tedious. This is an experimental research. The subject of the study is limited to the students of the sixth year of SDN 1 Tuntang, which has 27 students as the sample. She focuses on teaching method, which gives emphasis on flashcards as media in teaching vocabulary. To prove the success of teaching the writer compares between the result pre-test and post-test. The findings of this study showed that there are 20 students or 60 % are categorized as excellent, 15, 6 % or 3 students are as good students, 12, 5 % or 3 students are as fair, and 3, 1 % students are as poor. It means that teaching English vocabularies by using flashcards are very effective. Keywords: Teaching English Vocabulary; Flashcards; Visual Aids